Binding of beta gamma subunits of heterotrimeric G proteins to the PH domain of Bruton tyrosine kinase. - Tsukada, S (1994)
Bruton tyrosine kinase (Btk) has been implicated as the defective gene in both human and murine B-cell deficiencies. The identification of molecules that interact with Btk may shed light on critical processes in lymphocyte development. The N-terminal unique region of Btk contains a pleckstrin homology domain. This domain is found in a broad array of signaling molecules and implicated to function in protein-protein interactions. By using an in vitro binding assay and an in vivo competition assay, the pleckstrin homology domain of Btk was shown to interact with the beta gamma dimer of heterotrimeric guanine nucleotide-binding proteins (G proteins). A highly conserved tryptophan residue in subdomain 6 of the pleckstrin homology domain was shown to play a critical role in the binding. The interaction of Btk with beta gamma suggests the existence of a unique connection between cytoplasmic tyrosine kinases and G proteins in cellular signal transduction.